Postexercise hypotension and autonomic modulation response after full versus split body resistance exercise in trained men - de Freitas, Marcelo Conrado [UNESP]; Ricci-Vitor, Ana Laura [UNESP]; Quizzini, Giovanni Henrique [UNESP]; de Oliveira, João Vitor N.S. [UNESP]; Vanderlei, Luiz Carlos M. [UNESP]; Lira, Fabio Santos [UNESP]; Rossi, Fabrício Eduardo (Korean Society of Exercise Rehabilitation, 2018)
To investigate the effects of full versus split body resistance exercise on postexercise hypotension and autonomic modulation in trained men. Sixteen resistance recreationally trained males (age, 24.9±5.3 years) performed three randomized trials: upper body (UB), lower body (LB), and full body (FB) conditions. Blood pressure and heart rate variability were collected at rest, immediately postexercise, post-10, and post-30 min during recovery. For systolic blood pressure, delta (30 min minus rest) was lower for the FB condition compared to the UB (-10.1±7.4 mmHg [FB] vs. -3.3±12.6 mmHg [LB] vs. -1.9±8.1 mmHg [UB], P=0.004). For diastolic blood pressure (-8.2±10.9 mmHg [FB] vs. -1.5±9.8 mmHg [LB] vs. -8.7±11.4 mmHg [UB], P=0.038) and mean blood pressure delta during recovery (-11.7±14 mmHg [FB] vs. -2.2±10.6 mmHg [LB] vs. -5.2±6.8 mmHg [UB], P=0.045), there were statistically significant lower values in the FB condition in relation to the LB condition. Regarding heart rate variability, there were no significant differences between conditions, however, the square root of the mean squared difference between adjacent RR intervals presented an increase until post-30 during recovery (P < 0.001), and there was a higher values of low fre-quency and lower values of high frequency across time (P < 0.001). Postexercise hypotension was influenced by the amount of muscle mass involved in a bout of resistance exercise, with the FB condition in-ducing lower systolic blood pressure in relation to the UB after exer-cise, as well as a great decrease in postexercise diastolic and mean blood pressure compared with the LB. The autonomic modulation re-sponse was similar between conditions during recovery.
Keywords: Autonomic nervous system; Blood pressure; Strength exercise